Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538905
|View full text |Cite
|
Sign up to set email alerts
|

Identifying elementary students' pre-instructional ability to develop algorithms and step-by-step instructions

Abstract: The desire to expose more students to computer science has led to the development of a plethora of educational activities [16,7,15,4] and outreach programs to broaden participation in computer science. Despite extensive resources (time and money), they have made little impact on the diversity of students pursuing computer science. To realize large gains, computational thinking must be integrated into K-12 systems, starting with elementary school. In order to do so, existing resources need to be adapted for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Researchers have attempted to discover what CT concepts students use successfully at different ages [14,19,34]. In addition, several efforts have synthesized existing knowledge and research to guide future curriculum development.…”
Section: Ct Learning Trajectoriesmentioning
confidence: 99%
“…Researchers have attempted to discover what CT concepts students use successfully at different ages [14,19,34]. In addition, several efforts have synthesized existing knowledge and research to guide future curriculum development.…”
Section: Ct Learning Trajectoriesmentioning
confidence: 99%
“…We also tested prior knowledge for our algorithms learning progression strand. We found that, with little to no instruction, students were able to create an algorithm for sorting six canisters and identified the limitations of their algorithms when scaled to a larger number of items [11]. The students also struggled with the distinction between speeding up the algorithm and speeding up its implementation, so we adjusted our curriculum to go over this distinction [11].…”
Section: My Thesis Research Is Made Up Of Four Componentsmentioning
confidence: 99%
“…In contrast, Dwyer, Hill, Carpenter, Harlow, and Franklin (2014) focus on the sequence of steps chosen to solve a problem efficiently. They must consist of a finite number of exact instructions, terminate after a finite number of steps when applied to an input, and produce a correct answer when instructions are followed correctly.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Misfeldt and Ejsing-Dunn (2015) refer to "systematic descriptions of problem-solving and construction strategies, cause-effect relationships, and events." In contrast, Dwyer, Hill, Carpenter, Harlow, and Franklin (2014) focus on the sequence of steps chosen to solve a problem efficiently. Furthermore, within her much cited definition of computational thinking, Wing (2011) refers to algorithm as "an abstraction of a process that takes inputs, executes a sequence of steps, and produces outputs to satisfy a desired goal."…”
Section: Introductionmentioning
confidence: 99%